Crystal structure of bisoprolol fumarate Form I, (C18H32NO4) (C4H2O4)0.5. Issue 1 (March 2020) - Kaduk, James A.; Gindhart, Amy M.; Blanton, Thomas N.
Abstract : The crystal structure of bisoprolol fumarate Form I has been solved and refined using synchrotron X-ray powder diffraction data and optimized using density functional techniques. Bisoprolol fumarate Form I crystallizes in space group P -1 (#2) with a = 8.165 70(5) Å, b = 8.516 39(12) Å, c = 16.751 79(18) Å, α = 89.142(1)°, β = 78.155(1)°, γ = 81.763(1)°, V = 1128.265(10) Å 3, and Z = 2. The neutral side chain of the bisoprolol cation is probably disordered. The cation and anion are linked by N–H⋯O and O–H⋯O hydrogen bonds. The cations are also linked by N–H⋯O hydrogen bonds. The result is alternating layers of hydrophilic and hydrophobic layers parallel to the ab -plane. The density of the structure is relatively low at 1.130 g cm −3, but there are no obvious voids in the structure. The powder pattern is included in the Powder Diffraction File™ as entry 00-066-1625.